A Campylobacter integrative and conjugative element with a CRISPR-Cas9 system targeting competing plasmids: a history of plasmid warfare?. Issue 11 (12th November 2021) - van Vliet, Arnoud H. M.; Charity, Oliver J.; Reuter, Mark
Abstract : Microbial genomes are highly adaptable, with mobile genetic elements (MGEs) such as integrative conjugative elements (ICEs) mediating the dissemination of new genetic information throughout bacterial populations. This is countered by defence mechanisms such as CRISPR-Cas systems, which limit invading MGEs by sequence-specific targeting. Here we report the distribution of the pVir, pTet and PCC42 plasmids and a new 70–129 kb ICE (CampyICE1) in the foodborne bacterial pathogens Campylobacter jejuni and Campylobacter coli . CampyICE1 contains a degenerated Type II-C CRISPR system consisting of a sole Cas9 protein, which is distinct from the previously described Cas9 proteins from C. jejuni and C. coli . CampyICE1 is conserved in structure and gene order, containing blocks of genes predicted to be involved in recombination, regulation and conjugation. CampyICE1 was detected in 134/5829 (2.3 %) C . jejuni genomes and 92/1347 (6.8 %) C . coli genomes. Similar ICEs were detected in a number of non-jejuni/coli Campylobacter species, although these lacked a CRISPR-Cas system. CampyICE1 carries three separate short CRISPR spacer arrays containing a combination of 108 unique spacers and 16 spacer-variant families. A total of 69 spacers and 10 spacer-variant families (63.7 %) were predicted to target Campylobacter plasmids. The presence of a functional CampyICE1 Cas9 protein and matching anti-plasmid spacers was associated with the absence of the pVir, pTet and pCC42 plasmids (188/214 genomes, 87.9 %), suggesting that the CampyICE1-encoded CRISPR-Cas has contributed to the exclusion of competing plasmids. In conclusion, the characteristics of the CRISPR-Cas9 system on CampyICE1 suggests a history of plasmid warfare in Campylobacter .